Sikuba (Sirup Kulit Buah Naga) Alternatif Alami untuk Menjaga Kekebalan Tubuh - Pratiwi, Ervia; Astuti HT, Widya; Ramadhani, Anindya; Aisya, Nur; Fachri, Andi Muhammad; Samsinar, Samsinar (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Utilication dragon fruit skin to make herbal syrup that is worth selling. The aim of the student creativity program – entrepreneurship (PKM-K) is to generate student motivation to become an entrepreneur in making dragon fruit syrup into a business worth selling. The methods of implementing this program are input, process (production), output and evaluation. The result of this program is the input of conducting a market survey to find out market conditions. Next, a feasibility study will be carried out for a useful business. The last step is the selection of materials and the acquisition of places and the acquisition of places and locations that will support the production process. Process (production), the process of making dragon fruit peel syrup starting fromthe preparation of materials and tools until they are ready Output, namely the syrup from dragon fruit skin that is ready to be marketed. consumed and marketed to consumers. The last is evalution, which is a step that is carried out during the process when the product is ready. In the following, we convey the shortcomings of why consumers are not interested in consuming our products. The conclusion of the PKM-K program for Making Dragon Fruit Peel Syrup into a valuable processed product can provide skills to students to remain innovative and creative in processing dragon fruit peel into herbal syrup. we really look forward to this activity can be followed up, so that it can be an altenative additional family producer.